2001
DOI: 10.3758/bf03194921
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for ascending and descending hierarchical organization in spatial communication

Abstract: People prefer to order spatial information in a hierarchy of decreasing size of spatial unit when giving directions for finding objects and in a hierarchy of increasing size of spatial unit when providing descriptions of object locations (Plumert, Carswell, DeVet, & Ihrig, 1995). In five experiments, we examined whether people have a preference for ascending or descending organization when the task does not involve conveying spatial information to others. In Experiments 1-3, people learned the locations of obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In particular, adults are skillful in adapting the descriptive features they provide to match the needs of their listeners attempting to find their way through an environment. These findings confirm that direction giving and following are dynamic processes that depend on interactions between those providing directions, the recipients of such directions, and their experiences giving and following directions to navigate through environments (Hirtle & Heidorn, 1993;Montello, Hegarty, Richardson, & Waller, 2004;Newcombe & Huttenlocher, 2000;Plumert, Carswell, DeVet, & Ihrig, 1995, Plumert, Spalding, & Nichols-Whitehead, 2001Schober, 1993Schober, , 1995Shelton & McNamara, 2004;Taylor, Naylor, & Chechile, 1999). One limitation of the present project was its reliance on a tabletop model town.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, adults are skillful in adapting the descriptive features they provide to match the needs of their listeners attempting to find their way through an environment. These findings confirm that direction giving and following are dynamic processes that depend on interactions between those providing directions, the recipients of such directions, and their experiences giving and following directions to navigate through environments (Hirtle & Heidorn, 1993;Montello, Hegarty, Richardson, & Waller, 2004;Newcombe & Huttenlocher, 2000;Plumert, Carswell, DeVet, & Ihrig, 1995, Plumert, Spalding, & Nichols-Whitehead, 2001Schober, 1993Schober, , 1995Shelton & McNamara, 2004;Taylor, Naylor, & Chechile, 1999). One limitation of the present project was its reliance on a tabletop model town.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the nature of the wayfinding task faced by direction givers and receivers affects their interactions. For instance, Plumert, Carswell, DeVet, & Ihrig (1995) demonstrated that participants organize their descriptions differently when describing a space than when giving directions to a traveller (see also Golding et al, 1996;Plumert, Spalding, & Nichols-Whitehead, 2001;Taylor, Naylor, & Chechile, 1999). When describing the location of a coffee cup, for instance, people note that it is on the desk, in the office, on the fourth floor of the psychology building.…”
Section: Discussionmentioning
confidence: 99%
“…Adults appear to be quite sensitive to the goals of the listener in communication tasks (Klabunde & Porzel, 1998;Plumert, Carswell, DeVet, & Ihrig, 1995;Plumert, Spalding, & Nichols-Whitehead, 2001, Russell & Schober, 1999Schober, 1995). For example, Plumert et al (1995 have shown that the ordering of spatial information in directions for finding missing objects appears to be governed by the needs of the listener.…”
mentioning
confidence: 97%